Retroperitoneal laparoscopy management for ureteral fibroepithelial polyps causing hydronephrosis in children: A report of five cases. Issue 5 (October 2015) - Dai, L.N.; Chen, C.D.; Lin, X.K.; Wang, Y.B.; Xia, L.G.; Liu, P.; Chen, X.M.; Li, Z.R.
Summary: Introduction: Hydronephrosis is a common disease in children and may be caused by ureteral fibroepithelial polyps (UFP). Ureteral fibroepithelial polyps are rare in children and are difficult to precisely diagnose before surgery. Surgical treatment for symptomatic UFP is recommended. At the present institution, retroperitoneal laparoscopy has been used to treat five boys with UFP since 2006. Objective: To highlight the significance of UFP as an etiological factor of hydronephrosis in children and evaluate the applicative value of retroperitoneal laparoscopy in the treatment of children with UFP. Methods: Between 2006 and 2013 five boys underwent retroperitoneal laparoscopy at the present institution. They were identified with UFP by review of the clinical database. Detailed data were collected, including: radiographic studies, gross anatomical pathology, and pathology and radiology reports. All boys had been followed up at least every 6 months. Results: All of the boys were aged between 7 and 16 years (mean 9.8 years). The main symptoms were flank pain (all five) and hematuria (three). Radiographic examination showed that all of the boys presented with incomplete ureteral obstruction and hydronephrosis. The ureteral fibroepithelial polyps were located near the left UPJ or the left proximal ureter. All of the boys had the UFP removed: three underwent retroperitoneal laparoscopic dismembered Anderson–Hynes pyeloplasty and polypectomy, and two had retroperitoneal laparoscopic ureteral anastomosis. These polyps were all on the left side and between 15 and 35 mm in length (mean 22 mm) (Figure). All of the boys recovered well and were discharged from hospital. The postoperative histological report confirmed that the specimens were UFP. Hydronephrosis was periodically assessed by ultrasonography (using the same method as pre-surgical ultrasonography) after surgery. Mean follow-up was 33 months (range 6–58 months) and no complications were found afterwards. Conclusions: Ureteral fibroepithelial polyps are rare but rather important as they can cause UPJ obstruction, which often manifests as hydronephrosis. It is most important to confirm the site of ureteral obstruction before surgery as this may have an effect on the surgical management. It is recommended that UFP be successfully managed in children with retroperitoneal laparoscopy. Figure Intraoperative findings of ureteral fibroepithelial polyps and the gross samples.